Turnover of pyrimethaming in mice infected with sensitive and resistant Plasmodium Chabaudi measured by competitive binding assay - Thanaphorn Tanchareon (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 1986